PENGARUH MOTIVASI DAN KOMPETENSI TERHADAP PRESTASI AKADEMIK MAHASISWA - Muthmainnah Asmal (PT. Saha Kreasi Indonesia, 2026)
Academic achievement is an important indicator of the success of higher education implementation. Such achievement is influenced by various internal and external factors, including learning motivation and academic competence. This study aims to analyze the effect of learning motivation and competence on students’ academic achievement. This research employed a quantitative approach with an explanatory research design. The population consisted of all students of the Computer Science Study Program at Pancasakti University Makassar, with a total sample of 113 students selected using a total sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression with the assistance of SPSS software. The results indicate that learning motivation and competence have a positive and significant effect on students’ academic achievement, both partially and simultaneously. Learning motivation was found to have a more dominant influence compared to competence. The coefficient of determination shows that learning motivation and competence explain a substantial proportion of the variance in students’ academic achievement, while the remaining variance is influenced by other factors outside the research model. These findings highlight the importance of strengthening students’ motivation and developing their competencies in a sustainable manner to enhance learning quality and academic achievement in higher education.